1995
DOI: 10.1038/bjc.1995.484
|View full text |Cite
|
Sign up to set email alerts
|

Mammary cancer in transgenic mice expressing insulin-like growth factor II (IGF-II)

Abstract: S_rThe effect of insulhn-like growth factor II (IGF-II) on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(100 citation statements)
references
References 35 publications
2
97
1
Order By: Relevance
“…Transgenic mice overexpressing growth hormone have a higher frequency of breast cancer (Bates et al, 1995;Hadsell et al, 1996) and disruption of the IGF-1 gene seems to prevent breast tumor formation by viral oncogens (Sell et al, 1993). Human mechanistic studies of the effect of estrogen antagonist drugs on breast carcinogenesis have shown a direct link with IGF-1.…”
Section: Glycemic Index In Chronic Disease Ls Augustin Et Almentioning
confidence: 99%
“…Transgenic mice overexpressing growth hormone have a higher frequency of breast cancer (Bates et al, 1995;Hadsell et al, 1996) and disruption of the IGF-1 gene seems to prevent breast tumor formation by viral oncogens (Sell et al, 1993). Human mechanistic studies of the effect of estrogen antagonist drugs on breast carcinogenesis have shown a direct link with IGF-1.…”
Section: Glycemic Index In Chronic Disease Ls Augustin Et Almentioning
confidence: 99%
“…Overexpression of IGF-I (Hadsell et al, 2000) or IGF-II (Bates et al, 1995;Pravtcheva and Wise, 1998) in the mammary epithelium results in tumor development, albeit with long latency. Recently, mammary specific overexpression of a constitutively active IGF-IR (Carboni et al, 2005) or wildtype IGF-IR (Jones et al, 2007) has been shown to induce rapid tumor formation by 2 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of serum IGF-I and reduced levels of serum IGFBP-3 have been associated with an increased relative risk for breast cancer especially in premenopausal women under the age of 50 years (Hankinson et al, 1998). Finally, a direct association between IGF-I and IGF-II overexpression and mammary tumorigenesis has been established in transgenic mice (Bates et al, 1995;Pravtcheva and Wise, 1998;Hadsell et al, 2000).…”
Section: Introductionmentioning
confidence: 99%